Experimental Behavior of SIFCON Corbels: Perilaku Eksperimental SIFCON Corbels - Hanadi F. Frhaan; Aqeel Hatem Chkheiwer (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the performance of six Slurry Infiltrated Fiber Concrete (SIFCON) corbels with a constant steel fiber volume of 6%, under varying vertical loads. By altering the shear span-to-depth ratio (a/d) from 0.4 to 0.6 and utilizing different fiber types (hooked end and micro) and reinforcement configurations (2Ø12mm and 3Ø12mm), the research examines the impact on maximum and cracking load capacities of the corbels. Results indicate that the a/d ratio, along with fiber type and reinforcement choice, significantly influences the structural behavior, offering insights for enhancing SFRC corbels' design and efficiency in construction applications. Highlights: Shear Span Impact: Changing the shear span-to-depth ratio critically affects load capacity. Material Influence: Fiber types and reinforcement configurations alter load behavior. Design Implications: Results highlight the importance of design choices in enhancing SIFCON corbels' structural performance. Keywords: SIFCON, Corbels, Shear Span, Steel Fiber, Load Capacity